Using Cooperative Integrated Reading and Composition (CIRC) Model With Aldiko Book Reader to Improve the Reading Comprehension Achievement of the Elevent Year Students of SMA 2 Parepare - Hasan Hasan; M.N. Jamalia (Journal Peqguruang: Conference Series, 2019)
This thesis studies about Using Cooperative Integrated Reading and Composition (CIRC) Model with Aldiko Book Reader to Improve the Reading Comprehension Achivement of the Elevent Year Students of SMA Negeri 2 Parepare. There are two problem statements in this research, these are 1) Is the use of coperative integrated reading and composition (CIRC) model with Aldiko book reader efective to improve the reading comprehension achivement of the eleventh year students of SMA Negeri 2 Parepare? and 2) Are the student interested in learning reading using cooperative integrated reading and composition (CIRC) model with Aldiko book reader? This research used quasi-experimental method, that applied one experimental group and one control group in this research. The researcher used cluster random sampling technique which takes IPA 2 class as an experimental group and IPA 3 class as a control group. The total sample are 74 students. The data colled through pretest and posttest. The data analysis by using t-test. The result of this research finally showed that the students comprehension in reading text was 68.38 in their pretest, but increase in the posttest with mean score was 82.16. It means that the alternative hypothesis is accepted, which the t-test value was greater than t-table value. In the posttest, the t-test value is 6.589 while t-table value is 2.021. Based on the result of data analysis, the writer concludes that using cooperative integrated reading and composition (CIRC) model with Aldiko book reader effective to improve the reading comprehension achievement of the student in reading text.